THE ANALYSIS OF ANIMACY IN THE DOVOLJA MONASTERY GOSPEL (Heritage, 2026)
The grammatical category of animacy in contemporary Serbian language is a formal syncretism in accusative and genitive cases of the masculine forms of words with declension denominating living beings. Contrary to the acc. = gen. marker for the animate, the category of inanimacy implies the acc. = nom. overlap when denominating objects and other inanimate phenomena. The paper analyses the forms in which the grammatical category of animacy occurs in the Gospel found in the Dovolja Monastery, dating back to the period between 1387 and 1389 and comprising 220 pages of parchment. The Gospel contains fragments of the Gospel of Matthew and the Gospel of Luke, as well as the Gospel of Mark in its entirety. 44 constructions in the acc. = gen. form (marking animacy) and 68 constructions in the acc. = nom. form (marking inanimacy) functioning as direct objects have been selected from the manuscript.
Keywords: animacy, Serbo-Slavic language, case syncretism.